Rasionalitas penggunaan obat pada pasien PPOK di Puskesmas XYZ Jakarta - Lestari Nugrahini; Iyan Hardiana; Azura Syafira Thalita; Jerry Jerry; Taufani Taufani (Health Sciences and Pharmacy Journal, 2022)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic pulmonary disease characterized by the occurrence of obstruction or obstruction of air flow in the airway that is progressively non reversible or partially reversible. An evaluation study of drug use in chronic obstructive pulmonary disease patients has been conducted at the XYZ Jakarta Health Center for the period of July – December 2017. The purpose of this study is to find out the pattern of drug use and the suitability of COPD treatment in adult patients at the Outpatient Installation of Public Health center XYZ Jakarta for the period of January-June 2017 which includes gender and comorbidity. The research was carried out at the Outpatient Installation of Public Health center XYZ Jakarta in November-December 2017 with a research method using descriptive by looking at the medical record data of adult COPD patients with a retrospective method, and sampling was carried out using the purposive sampling method for the January-June 2017 period.  The results of the study at Public Health center XYZ Jakarta on patients with Chronic Obstructive Pulmonary Disease of which out of 115 people the most widely used use of COPD drugs in patients that were most widely used was Beta Agonist 2 with the drug name Salbutamol as many as 112 (26.05%) items and the most widely used dosage form was the tablet dosage form, which was 381 (89.23%). The severity of the use of COPD drugs in adult patients was based on the criteria of appropriate indications (99.64%), appropriate drugs (99.64%), and appropriate dosage (100%). The conclusion in this study was that the rationality of drugs use in COPD patients has still 0.36% irrational use in indications and drugs.